Problem Analysis and Evaluation of Science Instruction in the Implementation of the Merdeka Curriculum at the Senior High School Level - Nurmala Mustofa; Mahrus Mahrus; Syahrizal Mustofa; Zulmizan Zulmizan (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2026)
Implementing the Independent Curriculum in science learning requires a shift towards student-centered learning, but it still faces various obstacles in the field. This study aims to analyze the implementation and problems of science learning within the Independent Curriculum at SMAN 1 Kediri, including the planning, implementation, and evaluation of learning. This study used a qualitative case study design, employing semi-structured interviews and documentation with science teachers and the Vice Principal for curriculum. The results show that learning has led to collaborative activities and discussions, but has not been optimal in developing innovative teaching modules, implementing practicums due to limited laboratory facilities, and applying authentic assessments, which remain limited to formative and summative forms. In addition, low student motivation to learn and uneven teacher competence pose challenges to curriculum implementation. The conclusion of this study indicates that the implementation of science learning within the Independent Curriculum has not been optimal and still requires improvements in various aspects. The implications of this research emphasize the importance of improving teacher competence, optimizing authentic assessments, and revitalizing laboratory facilities to create more meaningful, contextual science learning that aligns with the principles of the Independent Curriculum.